Neutrophil gelatinase-associated lipocalin levels are U-shaped in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study: impact for mortality - Woitas, Rainer P.; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Grammer, Tanja B.; Krämer, Bernhard; März, Winfried (PLOS ONE, 2017)
Introduction Neutrophil gelatinase-associated lipocalin (NGAL) is a glycoprotein released by damaged renal tubular cells and mature neutrophils. It is elevated in kidney injury, but also in patients with coronary artery disease (CAD) and myocardial infarction. We investigated the prognostic value of NGAL for total and cardiovascular mortality in patients undergoing coronary angiography without history of renal insufficiency at inclusion into the study. Participants The LURIC study is an ongoing prospective cohort study of patients referred for coronary angiography and is designed to evaluate determinants of cardiovascular health. Results NGAL was determined in plasma of 2997 persons (mean age: 62.7 years; 69.7% men) with a follow up for 10 years. 2358 patients suffered from CAD and 638 did not-these patients served as controls. Stable CAD was found in 1408 and unstable CAD in 950 patients. Death rate from cardiovascular events and all causes was highest in patients within the 4th quartile of NGAL (≥56 ng/ml, p<0.001 vs third quartile), even after adjustment for age and gender. According to multivariable-adjusted Cox analysis adjusting for well-known cardiovascular risk factors, as well as lipid lowering therapy, angiographic CAD, and C-reactive protein we found patients in the highest NGAL quartile being at increased risk for cardiovascular (hazard ratio (HR) 1.33, 95%CI 1.05-1.67, p = 0.016) and all cause mortality (HR 1.29 95%CI 1.07-1.55, p = 0.007) compared to those in the third quartile. The lowest risk was seen in the third quartile of NGAL (41-56 ng/ml) suggesting a U-shaped relationship between NGAL and mortality. Further adjustment for creatinine abrogated the predictive effect of NGAL. However, the 3rd and 4th quartiles of NGAL were significantly associated with higher neutrophil counts, which were associated with CAD, non-ST elevation and ST-elevation myocardial infarction (p<0.05). Conclusions Plasma NGAL concentrations are mainly derived from neutrophils and do not predict mortality independent of renal function.
Gesehen am 20.09.2018